2022
DOI: 10.3390/electronics11020257
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Modeling Framework for Bearing Failure Prediction

Abstract: Rolling element bearings are a common component in rotating equipment, a class of machines that is essential in a wide range of industries. Detecting and predicting bearing failures is then vital for reducing maintenance and production costs due to unplanned downtime. In previous literature, significant efforts have been devoted to building data-driven health models from historical bearing data. However, a common limitation is that these methods are typically tailored to specific failure instances and have lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The academic research community has identified many PHM-related tasks [19,20], which will be referred to as PHM capabilities. Several PHM capabilities are defined in [21,22], including detecting ongoing equipment degradation, diagnosing the root cause of degradation, and predicting when maintenance will be necessary. General anomaly detection and repair quality assessment are other examples of PHM capabilities that may be enabled.…”
Section: Planning Methodologymentioning
confidence: 99%
“…The academic research community has identified many PHM-related tasks [19,20], which will be referred to as PHM capabilities. Several PHM capabilities are defined in [21,22], including detecting ongoing equipment degradation, diagnosing the root cause of degradation, and predicting when maintenance will be necessary. General anomaly detection and repair quality assessment are other examples of PHM capabilities that may be enabled.…”
Section: Planning Methodologymentioning
confidence: 99%
“…Therefore, a point exists where optimum cost savings can be achieved by scheduling equipment maintenance at the ideal point. Broadly, predictive maintenance models have been developed in an attempt to find this point [ 34 , 35 , 36 ] with the ultimate goal of enhancing yield, reducing unplanned downtime, and general improvement of manufacturing efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…One common approach to implementing predictive maintenance is to ‘sensorize’ equipment in an attempt to connect specific sensor output to critical performance metric information. For example, the use of vibration sensors to measure bearing performance inside a motor, where an optimal sensor location is found, and time-series vibration signals are analyzed to determine the point-of-failure of the bearings in industrial applications [ 34 , 36 ]. One other such example for maintenance of seals is a slit-valve door (BSV) seal described in a U.S. Patent [ 37 ], which is based on the use of sensors positioned on various locations of a slit valve door seal (Bonded Slit Valve, also known as BSV seal) that used external strain sensor data attached to the sealing product (along with other factors) to understand product lifetime, thus creating a seal lifetime monitoring system.…”
Section: Introductionmentioning
confidence: 99%
“…As an important part of the machinery manufacturing industry, bearings are applied to connect the rotating mechanisms and reduce friction damage between agents [1,2]. It is well known that bearing defects are one of the most common sources of failure in induction motors [3,4].…”
Section: Introductionmentioning
confidence: 99%